THE LAKATOSIAN METHODOLOGY IN TEACHING THE SURFACE AREA OF A CONE AND A STUDENT’S CONCEPTUAL TRANSITION - Ugorji Iheanachor Ogbonnaya; Chrysoula Dimitriou-Hadjichristou (Jurnal Infinity, 2022)
Although many scholars support the Lakatosian method of mathematics education for enhancing students learning, the use of the method to foster students’ transition from alternative to scientific conceptions in mathematics does not seem to have been a focus of any research. This study explored if the Lakatosian heuristic method of teaching could foster a students’ transition from alternative to scientific conceptions of the surface area of a cone. The study used a qualitative, exploratory single case study design to undertake an in-depth study of a student in the 11th grade at a secondary school in Cyprus. Data was collected through lesson observation and analyzed using deductive content analysis.  The study found that beginning from informal conjectures and proofs to more formal proofs the student was able to transit from alternative conception to the scientific conception of the surface area of a cone. The finding suggests that the Lakatosian method of mathematics can foster students’ conceptual understanding of some mathematical concepts.